Liability To Third Parties Due to State Aircraft Accidents According to International And National Air Law - Hanifaturrizqi, Yasmin Fara; Latipulhayat, Atip (Universitas Internasional Batam, 2023)
This research highlights the pressing issue of the absence of state aircraft regulations demanding immediate attention. The coexistence of civil and state planes in the same airspace necessitates a thorough understanding of their interaction. However, international and national legal instruments have largely neglected state aircraft, focusing primarily on regulating air transportation and navigation for civil aviation. The research methodology employed for this study was normative juridical, involving examining library materials or secondary data using deductive thinking methods. The study's findings are clear: Firstly, in international law, the Convention on Compensation for Damage Caused by Aircraft to Third Parties 2009 and the Convention on Compensation for Damage to Third Parties 2009, Resulting from Acts of Unlawful Interference Involving Aircraft 2009 should be the standard for compensating third parties for losses resulting from aircraft activities. Secondly, at the national level, Law No. 1 of 2009 concerning Aviation and Minister of Transportation Regulation No. 77 of 2011 concerning the Responsibility of Air Transport Carriers must be used as a benchmark for fair compensation for losses to third parties due to aircraft activities. Governments must step up and ensure the safety and well-being of their citizens.